2023
DOI: 10.3390/molecules28041716
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production of Active Photosynthetic and Biochemical Molecules in Silybum marianum L. Using Biotic and Abiotic Elicitors in Hydroponic Culture

Abstract: Elicitors are stressors that activate secondary pathways that lead to the increased production of bioactive molecules in plants. Different elicitors including the fungus Aspergillus niger (0.2 g/L), methyl jasmonate (MeJA, 100 µM/L), and silver nanoparticles (1 µg/L) were added, individually and in combination, in a hydroponic medium. The application of these elicitors in hydroponic culture significantly increased the concentration of photosynthetic pigments and total phenolic contents. The treatment with MeJA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 98 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…[ 63 ] showed improvements in phenolic contents in grapes through methyl jasmonate application. Additionally, other authors found that the elicitation of different plants with methyl jasmonate and/or ethephon led to changes in secondary metabolites [ 64 , 65 ]. This research indicates that the application of elicitors like methyl jasmonate, in combination with other compounds, can effectively enhance the accumulation of bioactive compounds in plants, regardless of their maturity stage.…”
Section: Discussionmentioning
confidence: 99%
“…[ 63 ] showed improvements in phenolic contents in grapes through methyl jasmonate application. Additionally, other authors found that the elicitation of different plants with methyl jasmonate and/or ethephon led to changes in secondary metabolites [ 64 , 65 ]. This research indicates that the application of elicitors like methyl jasmonate, in combination with other compounds, can effectively enhance the accumulation of bioactive compounds in plants, regardless of their maturity stage.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was collected (0.1 mL) and mixed with the suitable reagent. Using the standard curve of bovine serum albumin, the total protein content was calculated at 650 nm [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…After 5 min, 0.3 mL of AlCl3 (10%) and 0.2 mL of NaOH (1 mol L −1 ) were added to the abovementioned solution, and the final volume was increased to 10 mL by adding additional distilled water. The absorbance was measured at 510 nm against a blank using a spectrophotometer to determine the flavonoids [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%